The Synthesis of (Magnetic) Crosslinked Enzyme Aggregates With Laccase, Cellulase, β-Galactosidase and Transglutaminase - Hojnik Podrepšek, Gordana; Knez, Željko; Leitgeb, Maja (Frontiers in Bioengineering and Biotechnology, 2022)
Immobilized enzymes have been widely studied during the last few decades due to their high potential and biological applications in various industries, as drug metabolism, biodiesel and antibiotic production, bioremediation, and the food industry. In this research, the enzymes laccase, cellulase, β-galactosidase (β-gal) and transglutaminase (TGM), were immobilized by two different methods: crosslinked enzyme aggregates (CLEAs) and magnetic crosslinked enzyme aggregates (mCLEAs). The processes for CLEAs and mCLEAs preparation with different enzymes have been optimized, and the clusters’s properties were investigated. A review of the results on the synthesis of CLEAs in mCLEAs is described, thus emphasizing the difference between the two types of immobilization based on different enzymes. This comparative study, which represents the synthesis of crosslinked enzyme aggregates using different enzymes has not been performed so far. Moreover, the obtained activity of CLEAs and mCLEAs is presented, which is important for further use in different biocatalytic processes. Specifically, of a higher importance is the selection of enzymes involved in immobilization, as they belong to the three different most applicable enzymes (oxidoreductases, hydrolases and transferases). The study confirmed that the whole course of research work on optimization of enzyme immobilization depended on the type of enzyme and required a lot of knowledge and experience. Moreover, the prepared immobilized enzyme was exposed to the supercritical carbon dioxide (scCO2) at different temperatures and pressures to determine the effect of scCO2 on enzyme activity in immobilized form and enzyme stability in different immobilization forms. The catalytic performance of immobilized enzyme was tested, where the catalytic efficiency and long-term operational stability of mCLEAs were obviously superior to those of CLEAs. However, the higher activity observed for CLEAs compared to mCLEAs suggests a significant effect of magnetic nanoparticles in the stabilization of enzyme crosslinked aggregate structure.